2022
DOI: 10.3389/fendo.2022.847401
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Depletion of Gut Microbiota in Osteoporosis and Osteoarthritis: A Narrative Review

Abstract: Osteoporosis and osteoarthritis are common diseases in an aging society, are considered metabolic diseases, and affect the quality of life of older adults. In addition, the gut microbiome is considered an additional organ to regulate bone metabolism. In the past decade, people have been studying the relationship between gut microbiota and bone metabolism. The role and mechanism of the gut microbiota in regulating bone metabolism is very important to improve the development of osteoporosis and osteoarthritis. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 89 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Thus, comprehensive approaches, such as improvement of systemic peroxidation state, chronic inflammatory stress, and immune status, as well as regulation of bone homeostasis, should be taken into consideration for treating postmenopausal osteoporosis. Also, disrupted gut microbial homeostasis, iron metabolism, cellular aging and stress, advanced glycation end products, and microRNA contributed to the pathogenesis of osteoporosis (Che et al, 2020;Yang et al, 2020;Chandra and Rajawat, 2021;Ge et al, 2022;Guan et al, 2022). Thus, the influence of monotropein on these biological processes should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, comprehensive approaches, such as improvement of systemic peroxidation state, chronic inflammatory stress, and immune status, as well as regulation of bone homeostasis, should be taken into consideration for treating postmenopausal osteoporosis. Also, disrupted gut microbial homeostasis, iron metabolism, cellular aging and stress, advanced glycation end products, and microRNA contributed to the pathogenesis of osteoporosis (Che et al, 2020;Yang et al, 2020;Chandra and Rajawat, 2021;Ge et al, 2022;Guan et al, 2022). Thus, the influence of monotropein on these biological processes should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their role in regulating regulatory T cells, probiotics also help maintain the integrity of intestinal epithelial cells (51) , which is critical for separating commensal bacteria from mucosal immune cells. In osteoporosis, the integrity of intestinal epithelial cells is often compromised (52) , leading to the expansion of Th17 cells that produce osteoclastogenic inflammatory cytokines (53) . These cytokines promote the formation of bone-resorbing osteoclasts, leading to bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…GM is closely related to a variety of diseases including trauma repair, osteoporosis, and Parkinson's disease (Hu et al, 2016 ; Liu, Chen, et al, 2021 ; Zmora et al, 2019 ). In our previous studies, we found that gut microbiota depletion caused by antibiotics can alleviate the progression of OA (Guan et al, 2020 ; Guan, Luo, et al, 2022 ). Changes in the abundance of certain specific gut microbiota such as Desulfovibrionales and Ruminiclostridium often lead to the progression of osteoarthritis (Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 87%